Burkholderia Pseudomallei is genetically diverse in agricultural land in Northeast Thailand - Wuthiekanun, V; Limmathurotsakul, D; Chantratita, N; Feil, E; Day, N; Peacock, S (Public Library of Science, 2009)
Background The soil-dwelling Gram-negative bacterium Burkholderia pseudomallei is the cause of melioidosis. Extreme structuring of genotype and genotypic frequency has been demonstrated for B. pseudomallei in uncultivated land, but its distribution and genetic diversity in agricultural land where most human infections are probably acquired is not well defined. Methods Fixed-interval soil sampling was performed in a rice paddy in northeast Thailand in which 100 grams of soil was sampled at a depth of 30 cm from 10×10 sampling points each measuring 2.5 m by 2.5 m. Soil was cultured for the presence of B. pseudomallei and genotyping of colonies present on primary culture plates was performed using a combination of pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Principal Findings B. pseudomallei was cultured from 28/100 samples. Genotyping of 630 primary colonies drawn from 11 sampling points demonstrated 10 PFGE banding pattern types, which on MLST were resolved into 7 sequence types (ST). Overlap of genotypes was observed more often between sampling points that were closely positioned. Two sampling points contained mixed B. pseudomallei genotypes, each with a numerically dominant genotype and one or more additional genotypes present as minority populations. Conclusions Genetic diversity and structuring of B. pseudomallei exists despite the effects of flooding and the physical and chemical processes associated with farming. These findings form an important baseline for future studies of environmental B. pseudomallei.